Relationship between the electrical conductivity of milk and blood estrogen, progesterone and follicle diameter in oestrous cows - Aydin, Muhterem; Yuksel, Murat; Timurkan, Huseyin (Indian Veterinary Journal, 2007)
[Abstract Not Available]
Keywords: Subclinical Mastitis; Pregnancy Rate; Cattle; Heifers; Growth